THREE BUCKETS SYSTEM FOR FOOD STREET INDUSTRY. CASE STUDY IN BANDUNG AND PALEMBANG - Riyadi, Dony; Bangun, Yusuf Kusuma (Institut Pariwisata dan Bisnis Internasional, 2019)
Food Street has become an Industry in Indonesia with growth Manificiently year by year, Many Business Cities such as Bandung- Capital City of West Java and Palembang- Capital City of South Sumatera, Food street industry in Indonesia is very rapidly development, All major cities in Indonesia have main area for food street vendors, and has become part of Lifestyle, Cleanliness is a Important issue that Domestic and Foreign Tourists are very detail mentioned on this matter, Food Hygiene, This research emphasizes the Solution of Cleaning Equipment and Cooking Hygiene Problems, Three Buckets System is adopted from cleanliness procedure on cruise ship, with the Wash - Rinse and Sanitize System then the Hygiene Guarantee will be more effective.Based on 6 (six) Principles of Food Hygiene,one of mentioned is Hygiene of Cookware and Dinner wares,Use of the Three Buckets System at a Street Vendor using the Portable (Three Bucket System) Tool to make it easier for Street Merchants to use the tool at a cost that is not large.Of the 250 Respondents interviewed 90% stated that cleanliness is very important in considering buying decisions in the street vendors.Some obstacles faced by Food Street Vendors in maintaining cleanliness are the availability of clean running water, Places and costs incurred in making washing Equipment, with Three Buckets System is expected to be a solution in maintaining cleanliness so that customer health can be maintained with cleanliness of Cooking Equipment and Utensils till Dinner Wares.